Highly Graphitic, Mesoporous Carbon Materials as Electrocatalysts for Vanadium Redox Reactions in All-Vanadium Redox-Flow Batteries. Issue 11 (16th August 2018) - Rümmler, Stefan; Steimecke, Matthias; Schimpf, Sabine; Hartmann, Mark; Förster, Stefan; Bron, Michael
Abstract : Two new commercially available mesoporous graphitic carbon materials were oxygen-functionalized with 0.2 M potassium permanganate solution, 10 M nitric acid and a mixture of water, nitric and sulfuric acid in a ratio of 1:2:1, respectively. Heat treatment of the oxidized samples in the presence of urea as a nitrogen precursor at 800°C yielded nitrogen-containing surface functional groups. Functionalized samples are compared to the pristine materials with respect to structure and morphology using TGA, Raman spectroscopy, TEM and XPS. The degree of oxygen functionalization depends on the oxidation agent and is different for both materials. There is a weak correlation between the amount of oxygen functional groups and the amount of nitrogen implemented during urea treatment, with thermally more stable C-O oxygen groups leading to enhanced nitrogen incorporation. The samples show a considerable structural inhomogeneity as observed from Raman spectroscopy in a mapping mode collecting 300 spectra. Electrocatalytic activity toward the VO 2+ /VO2 + redox pair was determined by CV. The electrocatalytic activity of the materials is significantly increased after functionalization, however, surprisingly independent from the degree of functionalization. On the other hand, carbon structural properties seem to have a significant impact on activity.